Molecular Cloning, Characterization, and Expression Analysis of an Ecdysone Receptor Homolog in Teleogryllus emma (Orthoptera: Gryllidae). Issue 1 (22nd March 2015) - He, Hui; Xi, Gengsi; Lu, Xiao
Abstract : Ecdysteroids are steroid hormones that play important roles in the regulation of Arthropoda animal growth development, larvae ecdysis, and reproduction. The effect of ecdysteroids is mediated by ecdysteroid receptor (EcR). The ecdysone receptor (EcR) belongs to the superfamily of nuclear receptors (NRs) that are ligand-dependent transcription factors. Ecdysone receptor is present only in invertebrates and plays a critical role in regulating the expression of a series of genes during development and reproduction. Here, we isolated and characterized cDNA of the cricket Teleopgryllus emma (Ohmachi & Matsuura) (Orthoptera: Gryllidae) and studied mRNA expression pattern using real time-polymerase chain reaction. The full-length cDNA of T. emma EcR, termed TeEcR, is 2, 558 bp and contains a 5′-untranslated region of 555 bp and a 3′-untranslated region of 407 bp. The open reading frame of TeEcR encodes deduced 531-amino acid peptides with a predicted molecular mass of 60.7 kDa. The amino acid sequence of T. emma EcR was similar to that of known EcR especially in the ligand-binding domain of insect EcR. Real-time quantitative reverse transcription-polymerase chain reaction was performed to compare TeEcR mRNA expression level at the whole body and gonad during T. emma development. The data revealed that TeEcR mRNA is differentially expressed during T. emma development, with the highest expression level in late-instar larvae of the body and lowest in third instar. The levels of TeEcR transcripts also vary among gonads development, and levels in ovaries were higher than in testes at every developmental stage. These results suggest that TeEcR may have potential significance to regulate the morphological structure and gonad development of T. emma, due to its expression in different developmental periods.